The Symbiosis of Virtual Reality Exposure Therapy and Telemental Health: A Review - Ong, Triton; Wilczewski, Hattie; Soni, Hiral; Nisbet, Quinn; Paige, Samantha R.; Barrera, Janelle F.; Welch, Brandon M.; Bunnell, Brian E. (Frontiers in Virtual Reality, 2022)
Phobias and related anxiety are common and costly mental health disorders. Experts anticipate the prevalence of phobias will increase due to the COVID-19 pandemic. Exposure therapies have been established as effective and reliable treatments for anxiety, including recent innovations in virtual reality-based exposure therapy (VRET). With the recent advent of telemental health (TMH), VRET is poised to become mainstream. The combination of VRET and TMH has the potential to extend provider treatment options and improve patient care experiences. In this narrative review, we describe how recent events have accelerated VRET+TMH, identify barriers to VRET+TMH implementation, and discuss strategies to navigate those barriers.